An Overview on Cleaning Validation - Payal K, Patel (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTPharmaceuticals can be contaminated by potentially dangerous substances. Essential to establish adequate cleaning procedures. Cleaning procedure is the process of assuring that cleaning procedures effectively remove the potentially dangerous substances from equipment or facility below predetermined level.Key words: Validation protocol, Rinse, Swab.